Liver Hydrolysate Assists in the Recovery From Physical Fatigue in a Mouse Model - Osamu Nakagawasai; Kotaro Yamada; Wataru Nemoto; Masahiro Fukahori; Takeshi Tadano; Koichi Tan-No (Elsevier, 2013)
It is reported that liver hydrolysate (LH) enhances liver function. However, the effects of LH on physical fatigue are unknown. The aim of this study was to investigate the effect of LH on alterations in locomotor activity and energy metabolism such as 5'-AMP-activated protein kinase (AMPK), glycogen content, and blood lactic acid, after forced walking. Adult male ddY mice were used. Locomotor activity, AMPK phosphorylation, and glycogen content in the liver and soleus muscle, as well as blood lactic acid were determined following LH treatment before and/or after forced walking. The locomotor activity significantly decreased after forced walking for 3 h. Two administrations of LH (30 or 100 mg/kg) significantly increased the locomotor activity, while a single administration either before or after forced walking did not show any specific effect. Administering LH twice activated AMPK in the liver and soleus muscle. Glycogen levels significantly decreased in both the liver and soleus muscle after forced walking, whereas the blood lactate level significantly increased. In contrast, administering LH twice increased muscle glycogen and decreased blood lactic acid. These findings indicate that LH produced an anti-fatigue effect and that this effect appears to involve the efficient glycogen utilization through activation of AMPK. [Supplementary Figure: available only at http://dx.doi.org/10.1254/jphs.13084FP] Keywords:: liver hydrolysate, physical fatigue, 5'-AMP-activated protein kinase, glycogen, lactic acid